ANALISIS PRODUKTIVITAS PEMBUATAN KAIN GREY DENGAN PENDEKATAN METODE AMERICAN PRODUCTIVITY CENTER DAN COBB-DOUGLAS - Abdul Jalal; Helvi Kusumawati (Teknoin, 2016)
PT. Primissima is a company engaged in textile Bisang, producing gray cloth that was established in 1971. The purpose of this study to determine the level of productivity with the approach of the American method Productivity Center (APC) and the Cobb-Douglas particular weaving section. Next calculate the productivity index forecast to come on the method selected is the highest. The data collected in this study consisted of data from production (output), labor, material, energy, and capital. Methods American Productivity Center (APC) was used to calculate the index of productivity, profitability index and the index of price improvement. While the Cobb-Douglas method used to calculate the coefficient of the intercept and Return to Scale. From the research conducted, the total productivity index using American Productivity Center (APC) has decreased, with a productivity index of 96.00 partially in 2009 and 2011. The profitability of the total input decreased by an average of 47.98 in partial quarterly. Total input price index improvement on average decreased partially 0.50 per quarter. The results using the method Cobb-Douglas found that inputs affect the production process is the efficiency index for 2009 was 58,997,167.96, while the year 2010 was 8.499, and in 2011 was 36,179,393.57. The use of the elasticity of input for the year 2009 amounted to -0.549 labor, material amounted to 0,062, a total energy of 0.613, and a capital of 0.093. The use of the elasticity of input for the year 2010 amounting to -0.032 use of labor, material amounted to 0.595, an energy of 0.114, and a capital of 0.267. The use of the elasticity of input for the year 2011 amounting to -0.781 use of labor, material amounted to 0.602, an energy of 0.063 and capital.of 0.298.